PSYCHODRAMA ANALYSIS OF CHARACTER “JIM” IN NOVEL “INTO THE MAGIC SHOP” BY DR. JAMES R. DOTY - Ratna Sari Dewi; Bima Prana Chitra (Jurnal Scientia, 2022)
This research is the result of research on the type of psychodrama experienced by Jim, the compassion shown by Jim and the purpose of psychodrama to others as introduced by Jim in the novel Into the Magic Shop by DR. James R. Doty. This research used qualitative research methods in research design, data collection and data analysis to describe, summarize and recap, and evaluate data from literature studies of several journals, books, blogs and others related to existing psychological studies and psychoanalytic therapy, which are the essence of this research. The results of the research conducted found that Jim's experience was a spiritual experience intended for meditation and visualization, the affection shown by Jim was to teach psychodrama to others and the purpose of introducing psychodrama was to make others feel the spiritual experience itself. Based on the research results, the researcher concludes that Psychodrama is an action technique in changing our views for the better. Meditation and Visualization are used in psychodrama techniques, the goal of which is to gain awareness of oneself. The power of heart and mind will create our desires. the relationship of heart and mind can make us change our perception of ourselves to create our desire for Self-Improvement